Effect of MTA and CEM on Mineralization-Associated Gene Expression in Stem Cells Derived from Apical Papilla - Hajizadeh, Niusha; Madani ‎, Zahra Sadat; Zabihi ‎, Ebrahim; Golpour ‎, Moniyreh; Zahedpasha ‎, Amir; Mohammadnia ‎, Mousa (Iranian Endodontic Journal, 2019)
Introduction: This study assessed the effect of mineral trioxide aggregate (MTA) and calcium-enriched mixture (CEM) cement on odontogenic differentiation and mineralization of stem cells. Methods and Materials: After confirmation of stemness and homogeneity of stem cells derived from apical papilla (SCAPs) using flow cytometry, the cells were exposed for 3 weeks to either osteogenic medium (OS) or CEM extract+OS (CEM+OS) or MTA extract in OS (MTA+OS) or DMEM based regular culture media (negative control). Relative expression of alkaline phosphatase (ALP), dentine sialophosphoprotein (DSPP), osteocalcin (OSC), and osterix (SP7) were measured at days 14 and 21 using RT-qPCR method. At the same time points Alizarin Red staining method was used to assess mineralization potential of SCAPS. Gene expression changes analysis were made automatically using REST® software and a P<0.05 was considered significant. Results: After 2 weeks of exposure, expression of all genes were between 3 and 52 times the expression of GADPH (all were upregulated except SP7 in the control, P<0.05). After 3 weeks, relative expressions of the genes: ALP, SP7, DSPP, and OSC were respectively 275.9, 528.3, 98.4, and 603.7 times the expression of GADPH in the control group (OS). These were respectively 17.405, 29.2, 11.8, and 6.5 in CEM+OS group, and 163.8, 119.7, 102.5, and 723.9 in MTA+OS group. All of these were confirmed as upregulated (P<0.05) except for ALP and OSC of DM+CEM group. After 2 weeks, alizarin red staining showed similar mineralized nodules in OS, MTA+OS, and CEM+OS. In third week, larger nodules were seen in MTA+OS and OS, but not in CEM+OS. Conclusion: After 2 weeks, gene expressions were almost comparable in OS, CEM+OS, and MTA+OS. After 3 weeks, OS and MTA+OS upregulated genes much greater than in 2nd week. However, upregulation in CEM+OS might not increase in 3rd week compared to those in 2nd week. Keywords: Biomaterials; Calcium-Enriched Mixture (CEM Cement); Mineral Trioxide Aggregate; Relative Gene Expression; Retrograde Root Filling Materials; Stem Cells from Apical Papilla